Estrutura de sistema de custos e atributos da informação: um estudo com empresas brasileiras - Rodniski, Cleber Marcos (Universidade do Vale do Rio dos Sinos, 2013)
The aim of this work is to verify the relationship between the cost system structure and the characteristics of information quality generated in Brazilian companies. The motivation its accomplishment arose from a similar study conducted by Cohen and Kaimenaki (2011) with Greek companies. The structure of such systems is evaluated by the system’s ability in detailing cost information, disaggregating costs according to its behavior, calculating the variations and the frequency with which cost information is provided. The information quality is measured by observing the relevance, precision, timeliness, upgrade, compatibility, accuracy, reliability and usefulness of the information generated by the system. The research methodology is embodied in a descriptive study, conducted by a survey, using a quantitative approach. The study involved a sample of 124 companies listed among the top 1000 companies operating in Brazil and in the classification presented by Exame Maiores e Melhores magazine (2011). The results indicate high levels of use of the cost system by the analyzed companies and that the majority of this system’s characteristics make positive and statistically significant influence over the generated information quality. The study also confirmed the findings of Cohen and Kaimenaki (2011) that the cost calculation at client, product and cost center levels does not necessarily generate more relevance in information, however, unlike the Greek study, the system capacity in generating information according to user’s request presented positive and significantly associated with most of the investigated information attributes. Also in this study, the R2 presented values smaller than 51,0 which indicates that other characteristics of the cost systems should be checked in order to explain the generation of information with the investigated attributes.
Keywords: Gestão de custos; Sistemas de custos; Qualidade da informação; Cost management; Cost systems; Information quality; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis